PERAN STAKEHOLDER DALAM PENGEMBANGAN KAWASAN MASJID KUNO BAYAN BELEQ SEBAGAI DESTINASI WISATA WARISAN BUDAYA - Jodi Hariawan; Yusri Abdillah; Luchman Hakim (Profit: Jurnal Administrasi Bisnis, 2020)
Area of Masjid Kuno Bayan Beleq located in the Lombok island. Development in this sites areaÂ involves the tourism stakeholders consisting of government, private sector, and the local community. The purpose of this study were to identify the profile and tourism attractions, the role of stakeholders, and the supporting and inhibiting factors of stakeholder roles. This research applies descriptive qualitative method. Literature studies, observations, and interviews are the technique used to obtain the data needed. The result shows that area ofÂ Masjid Kuno Bayan Beleq has the potential of cultural heritage tourism. The development of this area that has been done include: (1) the development of tourist atrraction, accesibility and amenity. (2) the role of stakeholder include : local government, private sector and local community. The stakeholders roles include the provision of infrastructure, human resource development, local development andÂ promotion.Â Supporting factors are the involvement of local communities in the management and support of the Non Government organiztion. Inhibiting factors are Department of culture and tourism roles is not maximized, local communities as a professional tour players are still lacking, and there are no investors who investing for development of the sites area and lack of coordination from various stakeholders.